Antibacterial Activity of Cherry Leaf (Muntingia calabura L.) Extract on Porphyromonas gingivalis Growth - Muflikhah, Dewi; Shita, Amandia Dewi Permana; Astuti, Pudji (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Pathological inflamatory condition that often complained and neglected in Indonesian is periodontal disease . The main ethiology of periodontitis is dental plaque. Porphyromonas gingivalis is one of anaerobic Gram-negative bacteria which contained in dental plaque. Increase in P. gingivalis colony will escalate damage in periodontal tissues. One of the alternative to control microorganism growth is by antibacterial agents in cherry leaf based material which contain flavonoids, saponins and tannins as active subtance. Objective: The aim of this studyÂ was to determine the effect of cherry leaf extract to P. gingivalis growth and to determine the maximum concentration in inhibiting the growth of P. gingivalis. Methods: This research used experimental laboratories methods with the post test only control group design. This research used well diffusion with 8 samples of each group. BHI-A was filled into petridish and inoculated by P. gingivalis. The holes was made 5 mm diameter and was filled 20Î¼l cherry leaf extract concentration 100%, 50%, 25%, 12,5%, 6,25%, aquadest steril (K-) and Chlorhexidine (K+). Petridish was placed in desicator and incubator at 370C for 24 hours. Zone of inhibition were measured by using digital caliper. Result and Conclusion: Cherry leaf extract contain antibacterial effect which can inhibit P. gingivalis increase in number with maximum concentration of 100%.